2021
DOI: 10.1098/rstb.2020.0349
|View full text |Cite
|
Sign up to set email alerts
|

When the human brain goes diving: using near-infrared spectroscopy to measure cerebral and systemic cardiovascular responses to deep, breath-hold diving in elite freedivers

Abstract: Continuous measurements of haemodynamic and oxygenation changes in free living animals remain elusive. However, developments in biomedical technologies may help to fill this knowledge gap. One such technology is continuous-wave near-infrared spectroscopy (CW-NIRS)—a wearable and non-invasive optical technology. Here, we develop a marinized CW-NIRS system and deploy it on elite competition freedivers to test its capacity to function during deep freediving to 107 m depth. We use the oxyhaemoglobin and deoxyhaemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Information on subjects' physiological responses to stressors can be gathered through measurements of heart rate, blood flow and pressure (e.g. [43]), blood and tissue oxygenation [44,45] as well as electroencephalogram (EEG) data [46,47]. Physiologging technology is now advancing our understanding of the ecophysiology of flight [48][49][50], terrestrial locomotion [51,52], swimming [53] and diving [26,45,54].…”
Section: Current State Of Physiologgingmentioning
confidence: 99%
“…Information on subjects' physiological responses to stressors can be gathered through measurements of heart rate, blood flow and pressure (e.g. [43]), blood and tissue oxygenation [44,45] as well as electroencephalogram (EEG) data [46,47]. Physiologging technology is now advancing our understanding of the ecophysiology of flight [48][49][50], terrestrial locomotion [51,52], swimming [53] and diving [26,45,54].…”
Section: Current State Of Physiologgingmentioning
confidence: 99%
“…Measuring heart rate through haemoglobin concentration fluctuations also provides information on cardiac waveform, which can provide information such as proxies for changes in blood pressure and potentially proxies for changes in intracranial pressure dynamics [51]. Further, analysis of both [HbO] and [HbR] cardiac waveforms can be used to calculate percentage arterial blood oxygen saturation [52] as recently employed to estimate SpO 2 in deep freediving humans [53]. Changes in [HbO] and [HbR] also provide measures of relative blood volume and tissue-specific blood oxygenation [21].…”
Section: (E) Physiological Monitoringmentioning
confidence: 99%
“…Appropriate ruggedization/marinization while maintaining optical-integrity and appropriate attachment protocols is, therefore, required to allow fNIRS to be used on wild animals. Initial work on seals [21] and deep-diving humans [53], although restricted to single-channel systems, has shown that this is readily achievable even for extreme environmental conditions.…”
Section: (G) Development Considerations For An Animal-borne Functional Near-infrared Spectroscopy Loggermentioning
confidence: 99%
“…dairy cattle [45,46] and fishes [47,48]). For example, the portable and commercially available near infraRed spectroscopy data logging devices introduced in 2006 were originally designed for measuring muscle oximetry in sports athletes [49], but have now also been used to show anticipatory adjustments of blood flow prior to diving in seals [18,50,51]. A wide range of variables can be measured with current physiologging technologies, which includes heart rate [52][53][54][55][56], brain activity [57,58], tissue oxygenation [50,51], respiratory rhythms [59,60] and body temperature [61,62].…”
Section: Part Ii: the Present State-of-the-artmentioning
confidence: 99%